Positive plate and battery

By using ternary materials containing elements W and Y and conductive adhesives containing carbon nanotubes, the problem of poor structural stability of high-nickel positive electrode materials during circulation is solved, and the cycle stability and rate performance of the battery are improved.

CN119650581AActive Publication Date: 2025-03-18ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411841935.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-18
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The structural stability of high-nickel positive electrode materials during circulation is poor, resulting in a decrease in the deintercalation rate of lithium ions and the detachability of the adhesive, which in turn affects the cycle stability and rate performance of the battery.

Method used

The ternary material and a conductive adhesive are used. The ternary material consists of the first and second particles containing elements W and Y. The conductive adhesive contains carbon nanotubes and an adhesive layer. The adhesive layer is composed of bonding groups such as carboxyl groups, hydroxyl groups, amine groups and silyl groups, and complex groups such as cyano groups to ensure the fitness and adhesion of the adhesive layer.

Benefits of technology

The structural stability of the ternary material and the reversibility of lithium ions are improved, the bonding and cohesive force of the positive electrode active material layer is enhanced, and the cycle stability and rate performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650581A_ABST
    Figure CN119650581A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a positive plate and a battery comprising the positive plate. The positive plate comprises a positive current collector and a positive active material layer, the positive active material layer comprises a ternary material and a conductive binder, the conductive binder comprises a carbon nanotube and a bonding layer, the bonding layer comprises a bonding group and a complexing group, the bonding group comprises one or more of carboxyl, hydroxyl, amido and silyl, the complexing group comprises cyano, and the bonding group comprises one or more of carboxyl, hydroxyl, amido and silyl. The weight ratio of the bonding groups to the complexing groups is (5-8): 1, and the length-diameter ratio of the carbon nanotubes is 50-10000; the ternary material comprises first particles and second particles, the weight content of the element W in the first particles is 500 ppm to 3500 ppm, and the weight content of the element Y in the second particles is 200 ppm to 2000 ppm. The ternary material disclosed by the invention is relatively high in cycling stability, the bonding cohesion in the positive electrode active material layer is relatively high, and the cycling stability and the rate capability of the battery are relatively high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode sheet and a battery comprising the positive electrode sheet. Background Art

[0002] In recent years, lithium-ion batteries, as the main power source for modern electronic devices and electric vehicles, have paid great attention to high energy density and high cycle life. In lithium-ion batteries, high-nickel cathode materials are favored by the power tool market due to their low cost and high energy density, but at the same time, high-nickel cathode materials also have problems such as poor cycle stability. Summary of the invention

[0003] Research has found that high-nickel positive electrode materials have poor structural stability during the cycle, and lattice oxygen is easily released and cracks and / or defects are easily formed, which affects the reversibility of lithium ion insertion and extraction. In addition, the metal elements in high-nickel positive electrode materials are easily dissolved and react with the electrolyte, resulting in a reduction in the bonding effect of conventional binders (for example, oil-soluble binders represented by polyvinylidene fluoride (PVDF), polyimide (PI), and functional polymer binders). The positive electrode material is easily detached and the electrical contact fails, thereby reducing the battery's cycle stability and rate performance.

[0004] In order to solve the problem that the poor structural stability of the positive electrode material leads to a decrease in the rate of lithium ion insertion and extraction and a decrease in the bonding property of the binder, the present invention provides a positive electrode sheet and a battery comprising the positive electrode sheet. The ternary material of the present invention has high cycle stability, high reversibility of lithium insertion and extraction, and high bonding cohesion in the positive electrode active material layer, and the battery has high cycle stability and rate performance.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, the positive electrode active material layer comprises a ternary material and a conductive binder, the conductive binder comprises carbon nanotubes and a bonding layer located on at least part of the surface of the carbon nanotubes, the bonding layer comprises a bonding group and a complexing group, the bonding group comprises one or more of a carboxyl group, a hydroxyl group, an amine group and a silane group, the complexing group comprises a cyano group, the weight ratio of the bonding group to the weight of the complexing group is (5-8):1, and the aspect ratio of the carbon nanotubes is 50-10000;

[0006] The ternary material includes a first particle and a second particle, the first particle includes an element W, the weight content of the element W in the first particle is 500ppm-3500ppm, and the second particle includes an element Y, the weight content of the element Y in the second particle is 200ppm-2000ppm.

[0007] A second aspect of the present invention provides a battery, comprising the positive electrode sheet described in the first aspect of the present invention.

[0008] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0009] (1) In the present invention, by controlling the weight content of the element W in the first particle and the weight content of the element Y in the second particle, the structural stability of the ternary material is high, the lattice oxygen is not easy to escape, and cracks and / or defects are not easy to appear, which can improve the cycle performance of the battery and extend the service life of the battery;

[0010] (2) In the present invention, the bonding layer of the conductive binder in the positive electrode sheet includes a bonding group and a complexing group, which can improve the overall adhesion of the positive electrode active material layer while inhibiting the dissolution of the metal elements in the ternary material, reducing the side reaction between the metal elements and the electrolyte, increasing the lithium deintercalation rate of the ternary material, and improving the cycle performance of the battery;

[0011] (3) In the present invention, the bonding group and the complexing group in the conductive bonding layer can bond with the ternary material through van der Waals force, thereby improving the cycle stability of the battery, and the cyanide group can also improve the wettability of the electrolyte to the positive electrode sheet, thereby improving the rate performance of the battery;

[0012] (4) In the present invention, the carbon nanotubes in the conductive binder of the positive electrode sheet can improve the dynamic performance of the positive electrode sheet and enhance the rate performance of the battery.

[0013] Other features and advantages of the present invention will be described in detail in the following detailed description.

[0014] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Shown is a schematic structural diagram of the positive electrode sheet of the present invention. DETAILED DESCRIPTION

[0016] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not used to limit the present invention. In this article, unless otherwise specified, the data range includes the endpoints.

[0017] It should be noted that the numerical expressions such as "first" and "second" in the present disclosure are only used to distinguish different substances or usage methods, and do not represent the difference in order.

[0018] A first aspect of the present invention provides a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, the positive electrode active material layer comprises a ternary material and a conductive binder, the conductive binder comprises carbon nanotubes and a bonding layer located on at least part of the surface of the carbon nanotubes, the bonding layer comprises a bonding group and a complexing group, the bonding group comprises one or more of a carboxyl group, a hydroxyl group, an amine group and a silane group, the complexing group comprises a cyano group, the weight ratio of the bonding group to the weight of the complexing group is (5-8):1, and the aspect ratio of the carbon nanotubes is 50-10000;

[0019] The ternary material includes a first particle and a second particle, the first particle includes an element W, the weight content of the element W in the first particle is 500ppm-3500ppm, and the second particle includes an element Y, the weight content of the element Y in the second particle is 200ppm-2000ppm.

[0020] like Figure 1 As shown, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, and the positive electrode active material layer includes a ternary material and a conductive binder 03. The ternary material includes a first particle 01 and a second particle 02.

[0021] The conductive adhesive comprises carbon nanotubes and an adhesive layer located on at least a portion of the surface of the carbon nanotubes. The carbon nanotubes are conductive and the adhesive layer is adhesive, so the conductive agent has both conductivity and adhesiveness. The adhesive layer can be located on the entire surface of the carbon nanotubes or on a portion of the surface of the carbon nanotubes. Whether the adhesive layer is located on a portion of the surface of the carbon nanotubes or on the entire surface of the carbon nanotubes, the adhesive has little or no effect on the conductivity of the carbon nanotubes, so the carbon nanotubes are still conductive and can meet the conductivity requirements of the positive electrode sheet.

[0022] The ternary material may include a first particle and a second particle, wherein the first particle includes the element W, and the weight content of the element W in the first particle is controlled within the above range, and the W element can introduce a nano-sized spinel / rock salt crystal domain having electrochemical activity on the surface of the first particle, thereby inhibiting phase change and strain accumulation during the cycle process, thereby improving Li +The reversibility of embedding and de-embedding improves the surface stability of the first particle. The second particle includes element Y, and the weight content of element Y in the second particle is controlled within the above range. Element Y can form a YO bond with element O in the ternary material with a large bond energy, effectively inhibiting the escape of lattice oxygen, and can also slow down the transformation of the ternary material from a layered phase to a spinel phase during the cycle process, inhibiting the phase change of the ternary material, and reducing the volume change of the ternary material during the battery charge and discharge cycle, thereby stabilizing the bulk structure of the ternary material and inhibiting the occurrence of cracks or depressions in the second particle.

[0023] The ternary material includes a first particle and a second particle. By simultaneously controlling the weight content of the element W in the first particle and the weight content of the element Y in the second particle, the surface stability of the first particle and the structural stability of the second particle can be improved, thereby improving the structural stability of the ternary material. The bonding layer located on at least part of the surface of the carbon nanotube includes a bonding group and a complexing group. The bonding group includes one or more of a carboxyl group, a hydroxyl group, an amine group, and a silane group. The complexing group includes a cyano group, wherein the complexing group can form a strong complexing reaction with the transition metal element on the surface of the ternary material, prevent the dissolution of the metal element in the ternary material, reduce the lattice phase change on the surface of the ternary material, improve the structural stability of the ternary material, extend the cycle life of the battery, and at the same time reduce the side reaction of the dissolved metal element with the electrolyte, avoid the reduction of the bonding effect of the positive electrode active material layer, and can also further enhance the conductive binder and the ternary material through complexing. The bonding strength between the materials is improved, the bonding group can ensure the bonding of the positive electrode active material layer and maintain the structural stability of the conductive network skeleton, and the weight ratio of the bonding group to the complexing group is controlled to be (5-8):1 (for example, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1 or 8:1), which can make the bonding group and the complexing group achieve a higher degree of adaptability, while ensuring the overall bonding of the positive electrode active material layer, improving the structural stability of the ternary material, reducing the dissolution of metal elements, reducing the side reaction between the ternary material and the electrolyte, and increasing the lithium deintercalation rate of the ternary material, thereby improving the cycle stability of the battery. The aspect ratio of the carbon nanotubes in the conductive binder is 50-10000 (for example, 50, 100, 500, 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000 or 10000). The length-to-diameter ratio of carbon nanotubes is relatively large, and both ends of the carbon nanotubes can be evenly embedded in the positive electrode active material layer to form a conductive network skeleton in the positive electrode active material layer, thereby improving the electronic conductivity of the positive electrode sheet, improving the kinetic performance of the positive electrode sheet, and enhancing the rate performance of the battery.

[0024] The positive electrode active material layer includes a ternary material and a conductive binder, the conductive binder includes a carbon nanotube and a bonding layer located on the surface of the carbon nanotube, the bonding layer includes a bonding group and a complexing group, the bonding group may include one or more of a carboxyl group, a hydroxyl group, an amine group and a silane group, the complexing group may include a cyano group, the bonding group and the complexing group in the conductive bonding bonding layer can be bonded to the ternary material through van der Waals force, thereby forming a solid electrode structure, and the carbon nanotube has good flexibility, which can ensure that the ternary material will not fall off due to volume changes during circulation, thereby improving the cycle stability of the battery. In addition, the cyano group can also improve the wettability of the electrolyte to the positive electrode sheet, thereby improving the transmission rate of lithium ions and improving the rate performance of the battery.

[0025] Therefore, the structural stability (including surface stability and bulk stability) of the ternary material of the positive electrode sheet of the present invention is high, lattice oxygen and metal elements are not easy to escape, the side reaction between the ternary material and the electrolyte is reduced, the bonding effect of the positive electrode active material layer is high, and the electronic conductivity is high, so that the cycle performance and rate performance of the battery are improved.

[0026] In the present invention, by controlling the weight content of element W in one particle and the weight content of element Y in the second particle, and using a conductive binder including a bonding group and a complexing group and controlling the relationship between the two, the battery can have higher cycle stability and higher rate performance compared to the prior art. In order to further improve the effect, one or more of the technical features can be further optimized.

[0027] The weight content of the element W in the first particle can be 500ppm-3500ppm (for example, 500ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm or 3500ppm). When the weight content of the element W in the first particle is less than 500ppm, the effect of improving the cycle stability of the ternary material is weak; when the weight content of the element W in the first particle is higher than 3500ppm, the conductivity and gram capacity of the ternary material will be reduced.

[0028] The weight content of element Y in the second particle can be 200ppm-2000ppm (for example, 200ppm, 500ppm, 700ppm, 1000ppm, 1200ppm, 1500ppm, 1700ppm or 2000ppm). When the weight content of element Y in the second particle is less than 200ppm, the effect of element Y on the cycle stability of the ternary material layer is weak; when the weight content of element Y in the second particle is higher than 2000ppm, the lattice spacing on the surface of the ternary material is reduced, which hinders the Li + The diffusion of lithium ions affects the rate of lithium ion insertion and extraction.

[0029] In the present invention, the weight content of element W in the first particle and the weight content of element Y in the second particle can be measured by conventional methods in the art, such as ICP.

[0030] In one example, the aspect ratio of the carbon nanotubes is 1000-6000.

[0031] In one example, the average diameter of the carbon nanotubes is 6 nm-10 nm (eg, 6 nm, 6.5 nm, 7 nm, 7.5 nm, 8 nm, 8.5 nm, 9 nm, 9.5 nm, or 10 nm).

[0032] In the present invention, the average diameter of the carbon nanotubes can be obtained by testing in the following way: using a transmission electron microscope (TEM), randomly selecting at least 10 carbon nanotubes within a field of view, measuring the outer diameter of each carbon nanotube, and taking the average value.

[0033] In one example, the carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes.

[0034] In one example, the weight ratio of the multi-walled carbon nanotubes to the single-walled carbon nanotubes is (1-3):1 (e.g., 1:1, 1.3:1, 1.5:1, 1.8:1, 2:1, 2.3:1, 2.5:1, 2.8:1 or 3:1). Controlling the weight ratio of the multi-walled carbon nanotubes to the single-walled carbon nanotubes within the above range can achieve a higher degree of synergy between the multi-walled carbon nanotubes (long-range conductive agent) and the single-walled carbon nanotubes (short-range conductive agent) in the positive electrode sheet. By matching the long-range and short-range conductive agents, the conductive performance of the positive electrode sheet is further improved, and the battery rate is increased.

[0035] In one example, the ratio of the weight of the multi-walled carbon nanotubes to the weight of the single-walled carbon nanotubes is (1.5-2.5):1.

[0036] In one example, the weight percentage M of the multi-walled carbon nanotubes in the conductive adhesive is 9%-55% (e.g., 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or 55%).

[0037] In one example, the weight proportion M of the multi-walled carbon nanotubes in the conductive adhesive is 20%-40%.

[0038] According to a specific implementation, the weight proportion of the multi-walled carbon nanotubes in the conductive adhesive is 9%-55%, and the weight ratio of the multi-walled carbon nanotubes to the single-walled carbon nanotubes is (1-3):1.

[0039] According to a specific implementation, the weight proportion of the multi-walled carbon nanotubes in the conductive adhesive is 20%-40%, and the weight ratio of the multi-walled carbon nanotubes to the single-walled carbon nanotubes is (1.5-2.5):1.

[0040] In one example, in the conductive adhesive, the adhesive layer is distributed on the surface of the carbon nanotube in a dotted form.

[0041] In one example, a crosslinking degree D between the conductive adhesive and the ternary material is 0.1-0.5 (eg, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 or 0.5).

[0042] In one example, a crosslinking degree D between the conductive adhesive and the ternary material is 0.15-0.35.

[0043] In the present invention, the degree of crosslinking between the conductive binder and the ternary material represents the average number of conductive binders in contact with the surface of a single positive ternary material particle. It is understandable that the degree of crosslinking between the conductive binder and the ternary material is a dimensionless constant, which can be obtained by testing in the following way: within an area of ​​100 μm*100 μm on the surface of the positive electrode sheet, 50 particles of the ternary material are randomly selected, and the number of conductive binders in contact with the surface of each ternary material particle is calculated, and the degree of crosslinking between the conductive binder and the ternary material = (the sum of the number of conductive binders in contact with the surfaces of 50 ternary material particles) / 50.

[0044] In one example, the first particles include single crystal particles.

[0045] In one example, the first particle includes a chemical formula of Li x1 Ni a1 Co b1 Mn c1 M 1 d1 O2 substances. Chemical formula Li x1 Ni a1 Co b1 Mn c1 M 1 d1 The relationship between the elements in O2 conforms to the principle that the algebraic sum of the positive and negative valences of the elements in the compound is zero.

[0046] wherein 0.9≤x1≤1.1 (e.g., 0.9, 0.93, 0.95, 0.98, 1, 1.03, 1.05, 1.08, or 1.1).

[0047] a1 may be 0.9≤a1≤0.99 (e.g., 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, or 0.99).

[0048] b1 may be 0.01≤b1≤0.1 (eg, 0.01, 0.03, 0.05, 0.08, or 0.1).

[0049] c1 may be 0.01≤c1≤0.1 (eg, 0.01, 0.03, 0.05, 0.08, or 0.1).

[0050] d1 may be 0.01≤d1≤0.05 (eg, 0, 0.01, 0.02, 0.03, 0.04, or 0.05).

[0051] M 1 It may include element W and one or more of the following elements: Al, Zr, B, Y, Sr, Ti, Nb. 1 The first particles may be present in a doped form and / or in a coated form.

[0052] In one example, the weight content of the element W in the first particles is 1000 ppm to 3000 ppm.

[0053] In one example, the Dv of the first particle is 1 10 is 0.5μm-4μm (for example, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm or 4μm), Dv 1 50 is 1.2 μm-6 μm (e.g., 1.2 μm, 1.5 μm, 2 μm, 3 μm, 4 μm, 5 μm or 6 μm), Dv 1 90≤10μm (for example, 10μm, 9μm, 8μm, 7μm, 6μm, 5μm, 4μm, 3μm, 2μm, 1μm, 0.5μm or 0.1μm).

[0054] In the present invention, the Dv of the first particle 1 10. Dv 1 50 and Dv 1 90 can be obtained by testing with a laser particle size analyzer.

[0055] In one example, the weight proportion S of the first particles in the ternary material is 50%-100% (e.g., 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%).

[0056] In one example, the weight proportion S of the first particles in the ternary material is 60%-80%.

[0057] In one example, the second particles include polycrystalline particles.

[0058] In one example, the second particle includes a chemical formula of Li x2 Ni a2 Co b2 Mn c2 M 2 d2 O2 substances.

[0059] wherein 0.9≤x2≤1.1 (e.g., 0.9, 0.93, 0.95, 0.98, 1, 1.03, 1.05, 1.08, or 1.1).

[0060] a2 may be 0.8≤a2≤0.95 (e.g., 0.8, 0.83, 0.85, 0.88, 0.9, 0.93, or 0.95).

[0061] b2 may be 0.01≤b2≤0.2 (e.g., 0.01, 0.03, 0.05, 0.08, 0.1, 0.13, 0.15, 0.18, or 0.2).

[0062] c2 may be 0.01≤c2≤0.1 (eg, 0.01, 0.03, 0.05, 0.08, or 0.1).

[0063] d2 may be 0.01≤d2≤0.05 (eg, 0, 0.01, 0.02, 0.03, 0.04, or 0.05).

[0064] M 2 It may include element Y and one or more of the following elements: Al, Zr, B, Sr, W, Ti, Nb. 2 The first particles may be present in a doped form and / or in a coated form.

[0065] In one example, the weight content of the element Y in the second particles is 400 ppm to 1800 ppm.

[0066] In one example, the Dv of the second particle is 2 10 is 3 μm-16 μm (for example, 3 μm, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm or 16 μm), Dv 2 50 is 4μm-21μm (for example, 4μm, 5μm, 8μm, 10μm, 13μm, 15μm, 18μm, 20μm or 21μm), Dv 290≤25μm (for example, 25μm, 23μm, 20μm, 18μm, 15μm, 13μm, 10μm, 8μm, 5μm, 3μm, 1μm, 0.5μm, 0.1μm).

[0067] In the present invention, the Dv of the second particle 2 10. Dv 2 50 and Dv 2 90 can be obtained by testing with a laser particle size analyzer.

[0068] In one example, the second particles include a plurality of primary particles, and the particle size of the primary particles is 100nm-600nm (for example, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm or 600nm). In the present invention, the particle size of the primary particles can be obtained by testing by conventional methods in the art, such as by scanning electron microscopy (SEM), specifically: take a positive electrode sheet, test the particle size of the primary particles of all the second particles within the field of view at 7.3mm*10kX, take the average value, and obtain the particle size of the primary particles.

[0069] In one example, the weight percentage of the second particles in the ternary material is 0-50% (e.g., 0, 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%).

[0070] In one example, the weight proportion of the second particles in the ternary material is 20%-40%.

[0071] In one example, the ternary material includes a chemical formula of Li x Ni a Co b Mn c M d O2 substances. Chemical formula Li x Ni a Co b Mn c M d The relationship between the elements in O2 conforms to the principle that the algebraic sum of the positive and negative valences of the elements in the compound is zero.

[0072] wherein 0.8≤a≤0.95 (e.g., 0.8, 0.83, 0.85, 0.88, 0.9, 0.93, or 0.95).

[0073] In one example, 0.86≤a≤0.92.

[0074] In one example, the positive electrode sheet satisfies: 1.6≤a / D≤9.5 (for example, 1.6, 2, 3, 4, 5, 6, 7, 8, 9 or 9.5). The increase in nickel content helps to improve the energy density of the battery, but the increase in nickel content will lead to poor rate performance of the ternary material and poor cycle stability, and the electrical contact of the electrode sheet is prone to breakage during long cycles. The positive electrode sheet is controlled to satisfy the above relationship, and the conductive binder can achieve good bonding with the ternary material. The conductive binder includes carbon nanotubes, which construct a conductive network structure of the positive electrode active material layer. The ternary material and the conductive binder are tightly combined, which can enable the ternary material to maintain electrical connectivity during the cycle and reduce the loss of rate performance and gram capacity. When a / D is higher than 9.5, the ternary nickel content is higher or D is lower, and the adhesion between the ternary material and the conductive binder is poor. During the battery cycle, the ternary material is easily disconnected from the conductive binder, causing the electrical contact of the positive electrode to deteriorate, affecting the battery's cycle stability; when a / D is lower than 1.6, the capacity of the ternary material is lower and the battery's capacity density loss is greater.

[0075] In one example, the positive electrode sheet satisfies: 2.4≤a / D≤6.2.

[0076] In one example, the average particle size of the ternary material is 1.2-13.5 (e.g., 1.2, 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, or 13.5).

[0077] In one example, the average particle size of the ternary material is 2-9.5.

[0078] In the present invention, the average particle size of the ternary material can be tested by conventional methods in the art, such as by scanning electron microscopy (SEM). Specifically, take a positive electrode sheet, test the particle size of all ternary materials within the field of view at 7.3mm*10kX, take the average value, and obtain the average particle size of the ternary material.

[0079] In one example, the specific surface area of ​​the ternary material is 0.5 m 2 / g-1.5m 2 / g (for example, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g or 1.5m 2 / g).

[0080] In one example, the specific surface area of ​​the ternary material is 0.6 m 2 / g-1.2m 2 / g.

[0081] In one embodiment, the surface of the ternary material has a coating layer. The increase of Ni element means that there will be more unstable Ni ions on the surface of the ternary material, especially when charging, Ni ions continue to lose electrons and show higher oxidizing Ni 4+ , which can easily oxidize the organic solvent in the system and even oxidize the organic binder, leading to the degradation of the battery system. In order to further improve the surface stability of the ternary material, a coating layer is set on the surface of the ternary material to reduce the contact between the ternary material and the organic solvent and organic binder, thereby improving the cycle performance of the battery.

[0082] In one example, the coating layer has a thickness of 5 nm to 100 nm (eg, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, or 100 nm).

[0083] In one example, the coating layer has a thickness of 10 nm to 50 nm.

[0084] In the present invention, the thickness of the coating layer can be tested by conventional methods in the art, for example, by using a transmission electron microscope (TEM), randomly selecting at least 50 ternary material particles in the field of view, randomly selecting at least 10 sites on the surface of each particle, measuring the thickness of the coating layer corresponding to each site, and taking the average value.

[0085] According to a specific embodiment, the thickness of the coating layer is 5nm-100nm, and the aspect ratio of the carbon nanotube is 50-10000. When high nickel material is used as the positive electrode active material, due to its poor structural stability, the battery produces serious gas during the cycle. The reason for the serious gas production is that the activity of the surface of the ternary material increases with the increase of nickel content, which increases the risk of side reactions with the electrolyte, resulting in degradation of battery performance. Therefore, a coating layer can be set on the surface of the ternary material, which can not only increase the strength and surface stability of the ternary material, but also suppress the risk of side reactions with the electrolyte. However, if the coating layer is simply set on the surface of the positive electrode active material without controlling it, it will affect the transmission of lithium ions in the battery, thereby causing the battery's rate performance to deteriorate. Therefore, the inventors of the present invention have found through a lot of research that by controlling the thickness of the coating layer on the surface of the positive electrode active material and the aspect ratio of the carbon nanotubes, it is possible to improve the better high temperature cycle stability and have a better lithium ion transmission efficiency.

[0086] According to a specific embodiment, the complexing group in the conductive binder includes a cyano group, and the ternary material includes single crystal particles and polycrystalline particles. Compared with polycrystalline particles, single crystal particles have better structural stability and are not prone to cracks, but the transmission efficiency of lithium ions in single crystal particles is not as good as that of polycrystalline particles; the cyano group in the conductive binder can improve the wettability of the electrolyte to the positive electrode sheet and improve the transmission rate of lithium ions. Therefore, when the ternary material includes single crystal particles and polycrystalline particles, the cyano group of the conductive binder can improve the conduction of lithium ions, thereby improving the structural stability of the ternary material and the lithium ion deintercalation rate.

[0087] According to a specific embodiment, the Dv of the first particle 1 10 is 0.5μm-4μm, Dv 1 50 is 1.2μm-6μm, Dv 1 90≤10μm, the Dv of the second particle 2 10 is 3μm-16μm, Dv 2 50 is 4μm-21μm, Dv 2 90≤25μm. Controlling the particle sizes of the first particles and the second particles to satisfy the above range formula can enable the first particles and the second particles to maintain a relatively stable bulk structure and surface structure during the battery charge and discharge cycle, thereby improving the high temperature cycle stability of the battery.

[0088] According to a specific embodiment, the Dv of the first particle 1 50 is 1.2μm-6μm, and the Dv of the second particle 2 50 is 4μm-21μm. When the median particle size of the first particle and the second particle meets the above range, the large and small particles can fill each other, the space utilization of the positive electrode sheet is improved, and the compaction density of the electrode sheet is improved, thereby reducing the polarization of the positive electrode sheet and improving the battery energy density.

[0089] According to a specific embodiment, the bonding layer includes a bonding group and a complexing group, the bonding group includes one or more of a carboxyl group, a hydroxyl group, an amine group and a silane group, the complexing group includes a cyano group, and the specific surface area of ​​the ternary material is 0.5 m 2 / g-1.5m 2 / g. The active sites on the surface of the ternary material increase with the increase of the specific surface area of ​​the ternary material, and the active sites can be in direct contact with the carbon nanotubes, thereby ensuring sufficient dispersion of the carbon nanotubes and helping to form a stable conductive network with excellent connectivity. Therefore, when the ternary material has the above-mentioned specific surface area range, the functional groups of the bonding layer on the surface of the conductive adhesive can be in closer contact with the active sites of the ternary material, thereby improving the adhesion and electrical connectivity of the positive electrode sheet, so that the lithium ion transmission efficiency can be maintained at a high level during the cycle, and the ternary material will lose less power during the cycle, further improving the cycle stability of the battery.

[0090] In one example, the positive electrode sheet satisfies the following relationship: 0.9≤S / M≤11.2, wherein S is the weight proportion of the first particle in the ternary material, in %, and M is the weight proportion of the multi-walled carbon nanotubes in the conductive binder, in %. The first particle is a single crystal particle, which has high cycle stability, is not prone to cracks, and can improve the compaction density of the positive electrode sheet. When the positive electrode sheet satisfies the above relationship, the mechanical properties of the positive electrode active material layer are good, the carbon nanotubes and the ternary material can be fully connected, so that the conductive network of the carbon nanotubes can play a greater effect, the conductivity of the positive electrode sheet is better, the polarization of the battery is small, and the energy density and rate capability are high.

[0091] In one example, the positive electrode sheet satisfies the following relationship: 1.5≤S / M≤4.

[0092] According to a specific embodiment, the weight proportion S of the first particles in the ternary material is 50%-100%, the weight proportion M of the multi-walled carbon nanotubes in the conductive adhesive is 9%-55%, and the positive electrode sheet satisfies the following relationship: 0.9≤S / M≤11.2.

[0093] According to a specific embodiment, the weight proportion S of the first particles in the ternary material is 60%-80%, the weight proportion M of the multi-walled carbon nanotubes in the conductive adhesive is 20%-40%, and the positive electrode sheet satisfies the following relationship: 0.9≤S / M≤11.2.

[0094] In one example, the weight ratio of the ternary material to the conductive binder is (99.4%-96%): (0.6%-4%). ​​It is understood that the weight ratio of the ternary material in the positive electrode active material layer can be in the range of 99.5%-96%, for example, 99.4%, 99%, 98.5%, 98%, 97.5%, 97%, 96.5% or 96%; the weight ratio of the conductive binder in the positive electrode active material layer can be in the range of 0.5%-4%, for example, 0.6%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5% or 4%, but it should be noted that the sum of the weight ratio of the ternary material in the positive electrode active material layer and the weight ratio of the conductive binder in the positive electrode active material layer needs to meet 100%.

[0095] By controlling the weight ratio of the ternary material to the conductive binder within the above range, the capacity retention rate of the battery during high temperature cycles, the mechanical stability of the positive electrode active material layer, and the compaction density of the positive electrode sheet can be improved through the combination of the ternary material and the conductive binder.

[0096] In one example, the compaction density of the positive electrode sheet is 3.1 g / cm 3 -3.6g / cm 3 (For example, 3.1 g / cm 3 、3.2g / cm 3 、3.3g / cm 3 、3.4g / cm 3 , 3.5g / cm 3 or 3.6g / cm 3 ).

[0097] In one example, the thickness of the positive electrode sheet is 40 μm-150 μm (eg, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm or 150 μm).

[0098] In one example, the thickness of the positive electrode sheet is 50 μm-120 μm.

[0099] In one example, the positive electrode sheet satisfies the following relational expression: 5 ≤ H / R ≤ 20 (for example, 5, 8, 10, 13, 15, 18, or 20), where H is the thickness of the positive electrode sheet in μm, and R is the average tube diameter of the carbon nanotubes in nm. When the thickness of the positive electrode sheet increases, the tube diameter of the carbon nanotubes in the conductive binder also needs to increase accordingly to maintain the mechanical stability of the positive electrode active material layer, optimize the conductive network, and reduce the agglomeration of carbon nanotubes. When the thickness of the positive electrode sheet decreases, the tube diameter of the carbon nanotubes in the conductive binder also needs to decrease accordingly; otherwise, it will cause a loss in the space utilization of the positive electrode active material layer and a decrease in the battery energy density. Controlling the positive electrode sheet to satisfy the above range can improve the conductivity of the positive electrode sheet, reduce the polarization of the positive electrode sheet, improve the electrical contact of the positive electrode active material, and increase the energy density and cycle stability of the battery.

[0100] In one example, the positive electrode sheet satisfies the following relational expression: 8 ≤ H / R ≤ 16, where H is the thickness of the positive electrode sheet in μm, and R is the average tube diameter of the carbon nanotubes in nm.

[0101] According to a specific embodiment, H is 40 - 150, R is 6 - 10, and the positive electrode sheet satisfies the following relational expression: 5 ≤ H / R ≤ 20, where H is the thickness of the positive electrode sheet in μm, and R is the tube diameter of the carbon nanotubes in nm.

[0102] According to a specific embodiment, H is 40 - 150, R is 6 - 10, and the positive electrode sheet satisfies the following relational expression: 8 ≤ H / R ≤ 16, where H is the thickness of the positive electrode sheet in μm, and R is the tube diameter of the carbon nanotubes in nm.

[0103] In one example, the conductive binder further includes a polymer additive.

[0104] In one example, the polymer additive includes one or more of polyamide, modified polyamide, and polyamide derivatives.

[0105] In one example, the molecular weight A of the polymer additive is 1000000 g / mol < A <2000000> g / mol.

[0106] In one example, the bonding layer in the conductive adhesive is formed by modifying carbon nanotubes with a modifier, and the modifier includes a first modifier and a second modifier, wherein the bonding group is provided by the first modifier, and the first modifier includes one or more of diethyl adipate, diethyl dimethylmalonate, diethyl suberate, dimethyl malonate, dimethyl suberate, methyl valerate, propyl butyrate, n-dodecyltrimethoxysilane, silane coupling agent, trimethylsilane, hexadecyltrimethylammonium tetrafluoroborate, N-(coconut alkyl)-N,N,N-trimethyl methylammonium sulfate, cocamidopropyl betaine hexadecyltrimethylammonium acetate and hexadecyltrimethylammonium nitrate; the complexing group is provided by the second modifier, and the second modifier includes one or more of polyacrylonitrile, poly(2-butenenitrile), poly(3-butenenitrile) and polymelamine.

[0107] In one example, based on the total weight of the positive electrode active material layer, the weight content of the carbon nanotubes is 0.25%-1.5%, the weight content of the bonding layer is 0.25%-1.5%, and the weight content of the polymer additive is 0.1%-1%.

[0108] A second aspect of the present invention provides a battery, comprising the positive electrode sheet described in the first aspect of the present invention.

[0109] The materials of the battery except the positive electrode sheet can be prepared according to the methods in the art, and can achieve the effects of improving the cycle stability and rate performance and extending the service life of the battery.

[0110] In one example, the battery further includes an electrolyte, and the electrolyte includes a cyanide-containing compound.

[0111] In one example, the cyano-containing compound includes one or more of 1,4-dicyano-2-butene, succinonitrile (SN), 1,3,6-hexanetrinitrile (HTCN), 1,4-dicyano-2,3-dimethyl-2-butene and 1,2,3-tris(2-cyanoethoxy)propane;

[0112] In one example, based on the total weight of the electrolyte, the weight content of the cyano-containing compound is 1%-10% (e.g., 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%).

[0113] In one example, the electrolyte further includes a lithium salt, an organic solvent and an additive.

[0114] In one example, the lithium salt includes one or more of lithium fluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium bisfluorosulfonyl imide (LiTFSI), lithium bistrifluoromethylsulfonyl imide, lithium difluorobisoxalatophosphate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(pentafluoroethylsulfonyl)imide, lithium tris(trifluoromethylsulfonyl)methyl lithium and lithium bis(trifluoromethylsulfonyl)imide. Lithium salt determines the basic physical and chemical properties of the electrolyte and is the most important component in the electrolyte that affects the characteristics of lithium-ion batteries. It can conduct lithium ions and increase the conductivity of the electrolyte.

[0115] In one example, the organic solvent includes ethylene carbonate (EC), propylene carbonate (PC) and at least one of the following solvents: propyl propionate (PP), ethyl propionate (EP), ethyl butyrate (EB), ethyl acetate (EA), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC).

[0116] EC in organic solvents can participate in the formation of SEI film during the first charge and discharge cycle of the battery, which can improve the efficiency of subsequent lithium ion deintercalation at the negative electrode and reduce the occurrence of side reactions. PC has a high dielectric constant, which can promote the dissociation of lithium salts and greatly improve the ionic conductivity in the solution.

[0117] In one example, the additive includes one or more of fluoroethylene carbonate (FEC), 1,3-propane sultone (PS), 1,3-acrylonitrile lactone (PST), vinylene carbonate (VC) and vinyl ethylene carbonate (VEC). The additive can form a film on the surface of the positive electrode / negative electrode to protect the positive electrode / negative electrode.

[0118] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 5%-21% (for example, 5%, 7%, 10%, 12%, 15%, 17%, 20% or 21%), the weight content of the organic solvent is 54%-89% (for example, 54%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 89%), and the weight content of the additive is 5%-25% (for example, 5%, 7%, 10%, 12%, 15%, 17%, 20%, 22% or 25%).

[0119] In one example, the battery further includes a negative electrode sheet and a separator.

[0120] The negative electrode sheet may be a conventional negative electrode sheet in the art.

[0121] The separator may be a conventional separator in the art.

[0122] In one example, the battery is a lithium-ion secondary battery.

[0123] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0124] The following examples are used to illustrate the positive electrode sheet and battery of the present invention.

[0125] Example 1

[0126] (1) Positive electrode

[0127] Ingredients preparation: Aluminum foil;

[0128] Positive electrode active material layer: ternary material (including first particles and second particles, the chemical formula of the first particle is LiNi 0.93 Co 0.04 Mn 0.01 M1 0.02 O2, M1 is W, B and Zr, the weight content of element W in the first particle is 2000ppm, and the Dv of the first particle is 1 10 is 1.2μm, Dv 1 50 is 3.5μm, Dv 1 90 is 7.8μm, the weight percentage of the first particle in the ternary material is 60%; the chemical formula of the second particle is LiNi 0.9 Co 0.04 Mn 0.03 M2 0.03 O2, M2 is Y, Zr and Ti, the weight content of element Y in the second particle is 1200ppm, and the Dv of the second particle is 2 10 is 4.5μm, Dv 2 50 is 13μm, Dv 2 90 is 18.8μm, the particle size of the primary particle is 400nm, the weight of the secondary particle in the ternary material is 40%, the a in the chemical formula of the ternary material is 0.92, the average particle size of the ternary material is 5.4μm, and the specific surface area of ​​the ternary material is 0.963m 2 / g, the surface of the ternary material has a coating layer, the thickness of the coating layer is 35.2nm) 97.75 parts by weight, a conductive adhesive (the bonding group is a carboxyl group (provided by the first modifier propyl butyrate), the complexing group is a cyano group (provided by the second modifier polyacrylonitrile), the weight ratio of the bonding group to the weight of the complexing group is 6.5, and the bonding layer is 1 part by weight; the aspect ratio of the carbon nanotubes is 3500, the average tube diameter R of the carbon nanotubes is 6nm, the weight proportion M% of the multi-walled carbon nanotubes in the conductive adhesive is 24.1%, the weight ratio of the multi-walled carbon nanotubes to the single-walled carbon nanotubes is 2.1, the carbon nanotubes are 0.8 parts by weight, the polymer additive is polyamide, the molecular weight of the polymer additive is 1780000, the polymer additive is 0.45 parts by weight, and the correlation D between the conductive bonding and the ternary material is 0.2) 2.25 parts by weight;

[0129] Preparation: The ternary material and the conductive binder are mixed evenly, and N-methylpyrrolidone (NMP) is added to obtain a positive electrode slurry with a solid content of 65%; the positive electrode slurry is evenly applied to the surface of both sides of a 10 μm aluminum foil using a coater, and the positive electrode sheet is obtained after drying, rolling, die-cutting, and sheeting.

[0130] Among them, the compaction density of the positive electrode is 3.45g / cm 3 , the thickness H of the positive electrode sheet is 90 μm, H / R=90 / 6=15, a / D=0.92 / 0.2=4.6, S / M=60 / 24.1=2.49.

[0131] (2) Negative electrode

[0132] Artificial graphite, silicon carbon, single-walled carbon nanotubes, multi-walled carbon nanotubes, styrene-butadiene rubber and sodium carboxymethyl cellulose are uniformly mixed in a mass ratio of 81:15.1:0.25:0.15:2.9:0.6 to obtain a material, ethylene carbonate accounting for 1% of the total material mass is added, and deionized water is added to obtain a negative electrode slurry (solid content is 45%); the negative electrode slurry is uniformly coated on both sides of a 5 μm high-strength carbon-coated copper foil, and after drying, it is rolled, die-cut and sheet-formed to obtain a negative electrode sheet.

[0133] (3) Electrolyte

[0134] In a glove box filled with inert gas (argon) (H2O<0.1ppm, O2<0.1ppm), an organic solvent (including ethylene carbonate, propylene carbonate, diethyl carbonate and propyl propionate totaling 76.5 parts by weight, wherein the mass ratio of ethylene carbonate: propylene carbonate: diethyl carbonate: propyl propionate is 15:10:10:65) is mixed evenly, and then fully dried lithium hexafluorophosphate (13 parts by weight) is quickly added thereto and stirred evenly, and finally fluoroethylene carbonate (7 parts by weight) and 1,2,3-tris(2-cyanoethoxy)propane (3.5 parts by weight) are added, and after passing the moisture and free acid tests, the desired electrolyte is obtained.

[0135] (4) Lithium-ion battery

[0136] The positive electrode sheet prepared in step (1), the negative electrode sheet prepared in step (2) and the separator (comprising a 5 μm thick polyethylene substrate, a 1 μm thick ceramic layer on one side of the substrate, and a 1.5 μm thick polyvinylidene fluoride adhesive layer on the other side of the substrate) are wound by a winding machine to obtain a battery core in which the positive and negative electrode sheets are separated by the separator, and then a lithium-ion secondary battery is obtained through welding, packaging, liquid injection, formation, air bag cutting, sorting and other processes.

[0137] Example 2

[0138] (1) Positive electrode

[0139] Ingredients preparation: Aluminum foil;

[0140] Positive electrode active material layer: ternary material (including first particles and second particles, the chemical formula of the first particle is LiNi 0.93 Co 0.04 Mn 0.01 M1 0.02 O2, M1 is W and Ti, the weight content of element W in the first particle is 1462ppm, and the Dv of the first particle 1 10 is 0.5μm, Dv 1 50 is 1.2μm, Dv 1 90 is 3.3μm, the weight percentage of the first particle in the ternary material is 75%; the chemical formula of the second particle is LiNi 0.9 Co 0.04 Mn 0.03 M2 0.03 O2, M2 is Y and B, the weight content of element Y in the second particle is 500ppm, and the Dv of the second particle is 2 10 is 3μm, Dv 2 50 is 4μm, Dv 290 is 7.6μm, the particle size of the primary particle is 100nm, the weight of the secondary particle in the ternary material is 25%, the a in the chemical formula of the ternary material is 0.92, the average particle size of the ternary material is 2μm, and the specific surface area of ​​the ternary material is 15m 2 / g, the surface of the ternary material has a coating layer, the thickness of the coating layer is 10nm) 97.5 parts by weight, a conductive adhesive (the bonding group is an amine group (provided by the first modifier cocamidopropyl betaine), the complexing group is a cyano group (provided by the second modifier poly (3-butenenitrile)), the weight ratio of the bonding group to the weight of the complexing group is 7, and the bonding layer is 0.5 parts by weight; the aspect ratio of the carbon nanotubes is 1000, the average tube diameter R of the carbon nanotubes is 8nm, the weight proportion M% of the multi-walled carbon nanotubes in the conductive adhesive is 30.2%, the weight ratio of the multi-walled carbon nanotubes to the single-walled carbon nanotubes is 1.7, the carbon nanotubes are 1.2 parts by weight, the polymer additive is a modified polyamide, the molecular weight of the polymer additive is 1140000, the polymer additive is 0.8 parts by weight, and the correlation D between the conductive bonding and the ternary material is 0.3) 2.5 parts by weight;

[0141] Preparation: The ternary material and the conductive binder are mixed evenly, and N-methylpyrrolidone (NMP) is added to obtain a positive electrode slurry with a solid content of 65%; the positive electrode slurry is evenly applied to the surface of both sides of a 10 μm aluminum foil using a coater, and the positive electrode sheet is obtained after drying, rolling, die-cutting, and sheeting.

[0142] Among them, the compaction density of the positive electrode is 3.25g / cm 3 , the thickness H of the positive electrode sheet is 40 μm, H / R=40 / 8=5, a / D=0.92 / 0.3=3.06, S / M=75 / 30.2=2.48.

[0143] (2) The negative electrode sheet was prepared in accordance with Example 1.

[0144] (3) Electrolyte

[0145] In a glove box filled with inert gas (argon) (H2O<0.1ppm, O2<0.1ppm), an organic solvent (including ethylene carbonate, propylene carbonate, diethyl carbonate and propyl propionate totaling 77.9 parts by weight, wherein the mass ratio of ethylene carbonate: propylene carbonate: diethyl carbonate: propyl propionate is 15:10:10:65) is mixed evenly, and then fully dried lithium hexafluorophosphate (13 parts by weight) is quickly added thereto and stirred evenly, and finally fluoroethylene carbonate (7 parts by weight) and succinonitrile (2.1 parts by weight) are added, and after passing the moisture and free acid tests, the desired electrolyte is obtained.

[0146] (4) The lithium ion battery was prepared in accordance with Example 1.

[0147] Example 3

[0148] (1) Positive electrode

[0149] Ingredients preparation: Aluminum foil;

[0150] Positive electrode active material layer: ternary material (including first particles and second particles, the chemical formula of the first particle is LiNi 0.93 Co 0.04 Mn 0.01 M1 0.02 O2, M1 is W and Sr, the weight content of element W in the first particle is 3347ppm, and the Dv of the first particle 1 10 is 4μm, Dv 1 50 is 6μm, Dv 1 90 is 10μm, the weight percentage of the first particle in the ternary material is 55%; the chemical formula of the second particle is LiNi 0.9 Co 0.04 Mn 0.03 M2 0.03 O2, M2 are Y and Nb, the weight content of element Y in the second particle is 900ppm, and the Dv of the second particle is 2 10 is 16μm, Dv 2 50 is 21μm, Dv 2 90 is 25μm, the particle size of the primary particle is 600nm, the weight of the secondary particle in the ternary material is 45%, the a in the chemical formula of the ternary material is 0.92, the average particle size of the ternary material is 9μm, and the specific surface area of ​​the ternary material is 0.6m 2 / g, the surface of the ternary material has a coating layer, the thickness of the coating layer is 100nm) 97.1 parts by weight, a conductive adhesive (the bonding group is a hydroxyl group and a carboxyl group (provided by the first modifier dimethyl malonate), the complexing group is a cyano group (provided by polymelamine), the weight ratio of the bonding group to the weight of the complexing group is 5.5, and the bonding layer is 1.2 parts by weight; the aspect ratio of the carbon nanotubes is 140, the average tube diameter R of the carbon nanotubes is 10nm, the weight proportion M% of the multi-walled carbon nanotubes in the conductive adhesive is 38.1%, the weight ratio of the multi-walled carbon nanotubes to the single-walled carbon nanotubes is 1.5, the carbon nanotubes are 1.5 parts by weight, the polymer additive is a polyamide derivative, the molecular weight of the polymer additive is 1930000, the polymer additive is 0.2 parts by weight, and the correlation D between the conductive bonding and the ternary material is 0.45) 2.9 weight;

[0151] Preparation: The ternary material and the conductive binder are mixed evenly, and N-methylpyrrolidone (NMP) is added to obtain a positive electrode slurry with a solid content of 65%; the positive electrode slurry is evenly applied to both sides of a 10 μm aluminum foil using a coater, and the positive electrode sheet is obtained after drying, rolling, die-cutting, and sheeting.

[0152] Among them, the compaction density of the positive electrode is 3.25g / cm 3 , the thickness H of the positive electrode sheet is 150 μm, H / R=150 / 10=15, a / D=0.92 / 0.45=2.04, S / M=55 / 38.1=1.44.

[0153] (2) The negative electrode sheet was prepared in accordance with Example 1.

[0154] (3) Electrolyte

[0155] In a glove box filled with inert gas (argon) (H2O<0.1ppm, O2<0.1ppm), an organic solvent (including ethylene carbonate, propylene carbonate, diethyl carbonate and propyl propionate totaling 73.7 parts by weight, wherein the mass ratio of ethylene carbonate: propylene carbonate: diethyl carbonate: propyl propionate is 15:10:10:65) is mixed evenly, and then fully dried lithium hexafluorophosphate (13 parts by weight) is quickly added thereto and stirred evenly, and finally fluoroethylene carbonate (7 parts by weight) and 1,3,6-hexanetrinitrile (6.3 parts by weight) are added, and after passing the moisture and free acid tests, the desired electrolyte is obtained.

[0156] (4) The lithium ion battery was prepared in accordance with Example 1.

[0157] Example 4 Group

[0158] This group of examples is used to illustrate the effects produced when the bonding group is changed.

[0159] Example 4a

[0160] The same procedure is carried out as in Example 1, except that the bonding groups are hydroxyl groups (provided by the second modifier diethyl dimethylmalonate).

[0161] Example 4b

[0162] The same method is carried out as in Example 1, except that the bonding groups are carboxyl groups and amine groups (provided by the second modifiers diethyl adipate and hexadecyltrimethylammonium acetate).

[0163] Example 4c

[0164] The process is carried out in accordance with Example 1, except that the bonding group is a silane group (provided by the second modifier, a silane coupling agent).

[0165] Example 5 Group

[0166] This set of examples is used to illustrate the effects when the ratio of the weight of the bonding groups to the weight of the complexing groups is changed.

[0167] Example 5a

[0168] The same procedure is carried out as in Example 1, except that the ratio of the weight of the bonding groups to the weight of the complexing groups is 5.

[0169] Example 5b

[0170] The same procedure is carried out as in Example 1, except that the ratio of the weight of the bonding groups to the weight of the complexing groups is 8.

[0171] Example 6 Group

[0172] This group of examples is used to illustrate the effects produced when the weight ratio of multi-walled carbon nanotubes to single-walled carbon nanotubes is changed.

[0173] Example 6a

[0174] The method is carried out with reference to Example 1, except that the ratio of the weight of multi-walled carbon nanotubes to the weight of single-walled carbon nanotubes is 2.5, the average tube diameter R of the carbon nanotubes is 8 nm, the aspect ratio of the carbon nanotubes is 1000, the weight proportion M% of the multi-walled carbon nanotubes in the conductive binder is 25.4%, S / M=60 / 25.4=2.36, and in order to reduce the impact of the change in H / R, the thickness H of the positive electrode sheet is adjusted to 120 μm accordingly, and H / R=120 / 8=15.

[0175] Example 6b

[0176] The method is carried out with reference to Example 1, except that the weight ratio of multi-walled carbon nanotubes to single-walled carbon nanotubes is 1.5, the aspect ratio of the carbon nanotubes is 6000, the weight percentage M% of the multi-walled carbon nanotubes in the conductive adhesive is 21.3%, and S / M=60 / 21.3=2.81.

[0177] Example 6c

[0178] Refer to Example 1, except that the ratio of the weight of multi-walled carbon nanotubes to the weight of single-walled carbon nanotubes is 3, the average tube diameter R of the carbon nanotubes is 20.7 nm, the aspect ratio of the carbon nanotubes is 50, the weight proportion M% of the multi-walled carbon nanotubes in the conductive binder is 26.7%, S / M=60 / 26.7=2.25, and in order to reduce the impact of the change in H / R, the thickness H of the positive electrode sheet is adjusted to 150 μm accordingly, and H / R=150 / 20.7=7.2.

[0179] Example 6d

[0180] The method is carried out with reference to Example 1, except that the ratio of the weight of multi-walled carbon nanotubes to the weight of single-walled carbon nanotubes is 1, the average tube diameter R of the carbon nanotubes is 5.2 nm, the aspect ratio of the carbon nanotubes is 10000, the weight proportion M% of the multi-walled carbon nanotubes in the conductive binder is 17.8%, S / M=60 / 17.8=3.38, and in order to reduce the impact of the change in H / R, the thickness H of the positive electrode sheet is adjusted to 80 μm accordingly, and H / R=80 / 5.2=15.4.

[0181] Example 7 Group

[0182] This group of examples is used to illustrate the influence of the weight content of element W in the first particle.

[0183] Example 7a

[0184] The same process is carried out as in Example 1, except that the weight content of element W in the first particles is 1000 ppm.

[0185] Example 7b

[0186] The same process is carried out as in Example 1, except that the weight content of element W in the first particles is 3000 ppm.

[0187] Example 7c

[0188] The same process is carried out as in Example 1, except that the weight content of element W in the first particles is 500 ppm.

[0189] Example 7d

[0190] The same process is carried out as in Example 1, except that the weight content of element W in the first particles is 3500 ppm.

[0191] Example 8 Group

[0192] This group of examples is used to illustrate the influence produced when the weight content of element Y in the second particle is changed.

[0193] Example 8a

[0194] The same process is carried out as in Example 1, except that the weight content of element Y in the second particles is 400 ppm.

[0195] Example 8b

[0196] The same process is carried out as in Example 1, except that the weight content of element Y in the second particles is 1800 ppm.

[0197] Example 8c

[0198] The same process is carried out as in Example 1, except that the weight content of element Y in the second particles is 200 ppm.

[0199] Example 8d

[0200] The same process is carried out as in Example 1, except that the weight content of element Y in the second particles is 2000 ppm.

[0201] Example 9

[0202] The process is carried out in accordance with Example 1, except that the doping element M2 is Y, Al, Zr and Ti.

[0203] Example 10

[0204] The process is carried out in accordance with Example 1, except that the doping element M1 is W, B, Al and Zr.

[0205] Example 11 Group

[0206] This group of embodiments is used to illustrate the impact when a changes.

[0207] Example 11a

[0208] The same method as in Example 1 is used, except that a is 0.86 and the chemical formula of the first particle is LiNi 0.9 Co 0.07 Mn 0.01 M1 0.02 O2, the chemical formula of the second particle is LiNi0 .8 Co 0.09 Mn 0.08 M2 0.03 O2, a / D=0.86 / 0.2=4.3.

[0209] Example 11b

[0210] The same method as in Example 1 is used, except that a is 0.93 and the chemical formula of the first particle is LiNi 0.95 Co 0.02 Mn 0.01 M1 0.02 O2, a / D=0.93 / 0.2=4.65.

[0211] Example 11c

[0212] The same method as in Example 1 is used, except that a is 0.81 and the chemical formula of the first particle is LiNi 0.85 Co 0.09 Mn 0.02 M1 0.04 O2, the chemical formula of the second particle is LiNi 0.75 Co 0.13Mn 0.1 M2 0.02 O2, a / D=0.81 / 0.2=4.05.

[0213] Example 11d

[0214] The same method as in Example 1 is used, except that a is 0.95 and the chemical formula of the first particle is LiNi 0.96 Co 0.02 Mn 0.01 M1 0.01 O2, the chemical formula of the second particle is LiNi 0.93 Co 0.03 Mn0 .02 M20 .02 O2, a / D=0.95 / 0.2=4.75.

[0215] Example 12 Group

[0216] This group of embodiments is used to illustrate the impact when D changes.

[0217] Example 12a

[0218] The same process is carried out as in Example 1, except that D is 0.15, and a / D=0.92 / 0.15=6.12.

[0219] Example 12b

[0220] The same process is carried out as in Example 1, except that D is 0.35, and a / D=0.92 / 0.35=2.62.

[0221] Example 12c

[0222] The same process is carried out as in Example 1, except that D is 0.1, and a / D=0.92 / 0.1=9.2.

[0223] Example 12d

[0224] The same process is carried out as in Example 1, except that D is 0.5, and a / D=0.92 / 0.5=1.84.

[0225] Example 12e

[0226] The same process is carried out as in Example 1, except that D is 0.6, and a / D=0.92 / 0.6=1.53.

[0227] Example 12f

[0228] The same process is carried out as in Example 1, except that D is 0.

[0229] Example 13 Group

[0230] This group of embodiments is used to illustrate the impact when S changes.

[0231] Example 13a

[0232] The same process is carried out as in Example 1, except that S is 70, and S / M=70 / 24.1=2.9.

[0233] Example 13b

[0234] The same process is carried out as in Example 1, except that S is 70, and S / M=80 / 24.1=3.32.

[0235] Example 13c

[0236] The same process is carried out as in Example 1, except that S is 80, and S / M=50 / 24.1=2.07.

[0237] Example 13d

[0238] The same procedure is carried out as in Example 1, except that S is 100, S / M=100 / 24.1=4.15, a=0.93, and a / D=0.93 / 0.2=4.65.

[0239] Example 13e

[0240] The same process is carried out as in Example 1, except that S is 70, a=0.9, and a / D=0.9 / 0.2=4.5.

[0241] Example 14 Group

[0242] This group of embodiments is used to illustrate the impact when S / M changes.

[0243] Example 14a

[0244] Refer to Example 1, except that M=9, the weight proportion of the bonding layer in the positive electrode active material layer is 1.5%, the weight proportion of the polymer additive is 1%, the weight proportion of the carbon nanotubes is 0.4%, the weight ratio of the multi-walled carbon nanotubes to the single-walled carbon nanotubes is 1.88, the aspect ratio of the carbon nanotubes is 5620, S / M=60 / 9=6.67, and the weight ratio of the ternary material to the conductive binder is 97.1%:2.9%.

[0245] Example 14b

[0246] Refer to Example 1, except that M=55, the weight proportion of the bonding layer in the positive electrode active material layer is 0.25%, the weight proportion of the polymer additive is 0.1%, the weight proportion of the carbon nanotubes is 1.5%, the weight ratio of the multi-walled carbon nanotubes to the single-walled carbon nanotubes is 2.11, the aspect ratio of the carbon nanotubes is 3500, S is 50, S / M=50 / 55=0.91, and the weight ratio of the ternary material to the conductive binder is 98.15%:1.85%.

[0247] Example 14c

[0248] Refer to Example 1, except that M=9, the weight proportion of the bonding layer in the positive electrode active material layer is 1.5%, the weight proportion of the polymer additive is 1%, the weight proportion of the carbon nanotubes is 0.4%, the weight ratio of the multi-walled carbon nanotubes to the single-walled carbon nanotubes is 1.88, the aspect ratio of the carbon nanotubes is 5620, S is 100, S / M=100 / 9=11.11, a is 0.93, a / D=0.93 / 0.2=4.65, and the weight ratio of the ternary material to the conductive binder is 97.1%:2.9%.

[0249] Example 15 Group

[0250] This group of examples is used to illustrate the effects produced when the weight content of the cyanide-containing compound in the electrolyte changes.

[0251] Example 15a

[0252] The process is carried out in accordance with Example 1, except that the weight content of the cyano compound in the electrolyte is 1%.

[0253] Example 15b

[0254] The process is carried out in accordance with Example 1, except that the weight content of the cyano compound in the electrolyte is 10%.

[0255] Example 15c

[0256] The process is carried out in accordance with Example 1, except that the weight content of the cyano compound in the electrolyte is 15%.

[0257] Example 15d

[0258] The process is carried out in accordance with Example 1, except that the electrolyte does not contain a cyano compound.

[0259] Example 16 Group

[0260] This set of examples is intended to illustrate the effects that occur when the specific selection of the cyano-containing compound is changed.

[0261] Example 16a

[0262] The process is carried out in accordance with Example 1, except that the cyano compound is 1,4-dicyano-2,3-dimethyl-2-butene.

[0263] Example 16b

[0264] The same process is carried out as in Example 1, except that the cyano compound is 1,4-dicyano-2-butene.

[0265] Example 17 Group

[0266] This group of embodiments is used to illustrate the effects produced when the weight ratio of the ternary material to the conductive binder is changed.

[0267] Example 17a

[0268] Refer to Example 1, except that the weight proportion of the bonding layer in the positive electrode active material layer is 0.25%, the weight proportion of the carbon nanotubes is 0.25%, the weight proportion of the polymer additive is 0.1%, the weight proportion of the multi-walled carbon nanotubes in the conductive binder is 28.2%, and the ratio of the weight of the ternary material to the weight of the conductive binder is 99.4%:0.6%.

[0269] Example 17b

[0270] Refer to Example 1, except that the weight proportion of the bonding layer in the positive electrode active material layer is 1.5%, the weight proportion of the carbon nanotubes is 1.5%, the weight proportion of the polymer additive is 1%, the weight proportion of the multi-walled carbon nanotubes in the conductive binder is 25.4%, and the weight ratio of the ternary material to the conductive binder is 96%:4%.

[0271] Example 18 Group

[0272] This group of embodiments is used to illustrate the impact when H / R changes.

[0273] Example 18a

[0274] The same process is carried out as in Example 1, except that the thickness H of the positive electrode sheet is 120 μm, and H / R=120 / 6=20.

[0275] Example 18b

[0276] The same process is carried out as in Example 1, except that the thickness H of the positive electrode sheet is 40 μm, and H / R=40 / 6=6.7.

[0277] Example 18c

[0278] The same process is carried out as in Example 1, except that the thickness H of the positive electrode sheet is 50 μm, and H / R=50 / 6=68.3.

[0279] Comparative Example 1

[0280] Positive electrode active material layer: ternary material (including first particles and second particles, the chemical formula of the first particle is LiNi 0.93 Co 0.04 Mn 0.01 M1 0.02 O2, M1 is W, B and Zr, the weight content of element W in the first particle is 2000ppm, and the Dv of the first particle is 1 10 is 1.2μm, Dv 1 50 is 3.5μm, Dv 1 90 is 7.8μm, the weight percentage of the first particle in the ternary material is 60%; the chemical formula of the second particle is LiNi 0.9 Co 0.04 Mn 0.03 M2 0.03 O2, M2 is Y, Zr and Ti, the weight content of element Y in the second particle is 1200ppm, and the Dv of the second particle is 2 10 is 4.5μm, Dv 2 50 is 13μm, Dv 2 90 is 18.8μm, the particle size of the primary particle is 400nm, the weight of the secondary particle in the ternary material is 40%, the a in the chemical formula of the ternary material is 0.92, the average particle size of the ternary material is 5.4μm, and the specific surface area of ​​the ternary material is 0.963m 2 / g, the surface of the ternary material has a coating layer with a thickness of 35.2nm) 97.75 parts by weight, and a binder (polyvinylidene fluoride (PVDF)) 2.25 parts by weight.

[0281] Preparation: The ternary material and the binder are mixed evenly, and N-methylpyrrolidone (NMP) is added to obtain a positive electrode slurry with a solid content of 65%; the positive electrode slurry is evenly coated on both sides of the 10μm aluminum foil using a coating machine, and the positive electrode sheet is obtained after drying, rolling, die cutting, and sheeting. Among them, the compaction density of the positive electrode sheet is 3.45g / cm 3 , the thickness H of the positive electrode sheet is 90μm.

[0282] Comparative Example 2

[0283] The same process is carried out as in Example 1, except that the conductive adhesive does not include an adhesive layer.

[0284] Comparative Example 3

[0285] The same procedure is carried out as in Example 1, except that there are no bonding groups in the bonding layer.

[0286] Comparative Example 4

[0287] The same process is carried out as in Example 1, except that there is no complexing group in the adhesive layer.

[0288] Comparative Example 5

[0289] Refer to Example 1, except that the ratio of the weight of multi-walled carbon nanotubes to the weight of single-walled carbon nanotubes is 9, the average tube diameter R of the carbon nanotubes is 20 nm, the aspect ratio of the carbon nanotubes is 15, the weight proportion M% of the multi-walled carbon nanotubes in the conductive binder is 32%, S / M=60 / 32=1.88, and in order to reduce the impact of the change in H / R, the thickness H of the positive electrode sheet is adjusted to 150 μm accordingly, and H / R=150 / 20=7.5.

[0290] Comparative Example 6

[0291] Refer to Example 1, except that the ratio of the weight of multi-walled carbon nanotubes to the weight of single-walled carbon nanotubes is 9, the average tube diameter R of the carbon nanotubes is 4 nm, the aspect ratio of the carbon nanotubes is 12050, the weight proportion M% of the multi-walled carbon nanotubes in the conductive binder is 11.9%, S / M=60 / 11.9=5.06, and in order to reduce the impact of the change in H / R, the thickness H of the positive electrode sheet is adjusted to 60 μm accordingly, and H / R=60 / 4=15.

[0292] Comparative Example 7

[0293] The same procedure is followed as in Example 1, except that the first particles do not include the element W.

[0294] Comparative Example 8

[0295] The same procedure is followed as in Example 1, except that the second particles do not include element Y.

[0296] Test Case

[0297] The lithium ion batteries obtained in the embodiment and the comparative example were respectively subjected to the following tests:

[0298] 1. Energy density test

[0299] The mass of the batteries prepared in the embodiments and comparative examples was measured using a balance. The batteries were placed in a constant temperature environment at 25°C, charged at 0.5C, with a cut-off current of 0.02C and a cut-off voltage of 4.3V, and then discharged at a rate of 0.2C to 3.0V. The discharge capacity and voltage platform were recorded. The energy density was calculated using the formula: energy density = discharge capacity × voltage platform / mass. The results are recorded in Table 1.

[0300] 2. Ratio test

[0301] The batteries prepared in the examples and comparative examples were placed in a constant temperature environment at 25°C, charged at 0.5C with a cut-off voltage of 4.3V, and then discharged to 3.0V at 0.5C and 1C rates, respectively. The capacity data during the process were recorded, and the rate retention rate was obtained by dividing the 1C rate discharge capacity by the 0.5C rate discharge capacity. The results are recorded in Table 1.

[0302] 3. Cycle test

[0303] The batteries prepared in the examples and comparative examples were placed in a constant temperature environment of 45°C, charged at 2C with a cut-off voltage of 4.3V, and discharged at a rate of 5C with a cut-off voltage of 3.0V. The discharge capacity at this time was recorded as Q1, and the thickness of the battery was recorded as H1. This was considered a cycle. After 500 cycles, the discharge capacity at the 500th cycle was recorded as Q2, and the thickness of the battery was recorded as H2. The cycle capacity retention rate (discharge capacity) = Q2 / Q1×100%, and the cycle expansion rate = (H2-H1) / H1×100%. The results of the 500T cycle capacity retention rate and the cycle expansion rate are recorded in Table 1.

[0304] Table 1

[0305]

[0306]

[0307]

[0308] It can be seen from Table 1 that the positive electrode sheet of the embodiment has a higher cycle capacity retention rate, a lower cycle expansion rate, and a higher rate retention rate through the comparative examples and embodiments, indicating that the weight content of the element W in one particle and the weight content of the element Y in the second particle are controlled, and a conductive binder including a bonding group and a complexing group is used and the relationship between the two is controlled, thereby improving the cycle stability and rate performance of the battery.

[0309] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, the positive electrode active material layer comprises a ternary material and a conductive binder, the conductive binder comprises carbon nanotubes and a bonding layer located on at least part of the surface of the carbon nanotubes, the bonding layer comprises a bonding group and a complexing group, the bonding group comprises one or more of a carboxyl group, a hydroxyl group, an amine group and a silane group, the complexing group comprises a cyano group, the weight ratio of the bonding group to the weight of the complexing group is (5-8):1, and the aspect ratio of the carbon nanotubes is 50-10000; The ternary material includes a first particle and a second particle, the first particle includes an element W, the weight content of the element W in the first particle is 500ppm-3500ppm, and the second particle includes an element Y, the weight content of the element Y in the second particle is 200ppm-2000ppm.

2. The positive electrode sheet according to claim 1, wherein: The first particle includes a single crystal particle, and the first particle includes a chemical formula of Li x1 Ni a1 Co b1 Mn c1 M 1 d1 O2 substances, where 0.9≤x1≤1.1, 0.9≤a1≤0.99, 0.01≤b1≤0.1, 0.01≤c1≤0.1, 0≤d1≤0.05, M 1 It includes the element W and one or more of the following elements: Al, Zr, B, Y, Sr, Ti, Nb; And / or, the second particles include polycrystalline particles, the second particles include a chemical formula of Li x2 Ni a2 Co b2 Mn c2 M 2 d2 O2 substances, where 0.9≤x2≤1.1, 0.8≤a2≤0.95, 0.01≤b2≤0.2, 0.01≤c2≤0.1, 0≤d2≤0.05, M 2 It includes element Y and one or more of the following elements: Al, Zr, B, Sr, W, Ti, Nb; And / or, the diameter of the carbon nanotube is 6nm-10nm; and / or, the weight content of element W in the first particles is 1000ppm-3000ppm; And / or, the weight content of element Y in the second particles is 400 ppm to 1800 ppm.

3. The positive electrode sheet according to claim 2, wherein: The average particle size of the ternary material is 1.2-13.5, preferably 2-9.5; and / or, the Dv of the first particle 1 10 is 0.5μm-4μm, Dv 1 50 is 1.2μm-6μm, Dv 1 90≤10μm; and / or, the Dv of the second particle 2 10 is 3μm-16μm, Dv 2 50 is 4μm-21μm, Dv 2 90≤25μm; And / or, the second particles include a plurality of primary particles, and the particle size of the primary particles is 100 nm-600 nm.

4. The positive electrode sheet according to any one of claims 1 to 3, wherein: The ternary material includes a chemical formula of Li x Ni a Co b Mn c M d O2, wherein 0.8≤a≤0.95, preferably, 0.86≤a≤0.92; And / or, in the conductive adhesive, the adhesive layer is distributed on the surface of the carbon nanotube in a dotted form, and the crosslinking degree D between the conductive adhesive and the ternary material is 0.1-0.5, preferably 0.15-0.

35.

5. The positive electrode sheet according to claim 4, wherein: The positive electrode sheet satisfies: 1.6≤a / D≤9.5, preferably, 2.4≤a / D≤6.2; And / or, the specific surface area of ​​the ternary material is 0.5m 2 / g-1.5m 2 / g, preferably 0.6m 2 / g-1.2m 2 / g.

6. The positive electrode sheet according to any one of claims 1 to 3, wherein: The positive electrode sheet satisfies the following relationship: 0.9≤S / M≤11.2, wherein S is the weight proportion of the first particles in the ternary material, in %, and M is the weight proportion of the multi-walled carbon nanotubes in the conductive binder, in %. and / or, the weight proportion S of the first particles in the ternary material is 50%-100%, preferably 60%-80%; And / or, the carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes, and the weight proportion M of the multi-walled carbon nanotubes in the conductive adhesive is 9%-55%, preferably 20%-40%.

7. The positive electrode sheet according to claim 6, wherein: The weight ratio of the multi-walled carbon nanotubes to the single-walled carbon nanotubes is (1-3):1, preferably (1.5-2.5):

1.

8. The positive electrode sheet according to any one of claims 1 to 3, wherein: The thickness of the positive electrode sheet is 40 μm-150 μm, preferably 50 μm-120 μm; And / or, the aspect ratio of the carbon nanotubes is 1000-6000; And / or, the positive electrode sheet satisfies the following relationship: 5≤H / R≤20, wherein H is the thickness of the positive electrode sheet, in μm, and R is the diameter of the carbon nanotube, in nm; And / or, the surface of the ternary material has a coating layer, and the thickness of the coating layer is 5nm-100nm, preferably 10nm-50nm.

9. The positive electrode sheet according to any one of claims 1 to 3, wherein: The weight ratio of the ternary material to the conductive adhesive is (99.4%-96%): (0.6%-4%); And / or, the conductive binder further includes a polymer additive, the polymer additive includes one or more of polyamide, modified polyamide, and polyamide derivatives, and the molecular weight A of the polymer additive is 1000000 g / mol < A<2000000> g / mol; And / or, the bonding layer in the conductive adhesive is formed by modifying carbon nanotubes with a modifier, and the modifier includes a first modifier and a second modifier, wherein the bonding group is provided by the first modifier, and the first modifier includes one or more of diethyl adipate, diethyl dimethylmalonate, diethyl suberate, dimethyl malonate, dimethyl suberate, methyl valerate, propyl butyrate, n-dodecyltrimethoxysilane, silane coupling agent, trimethylsilane, hexadecyltrimethylammonium tetrafluoroborate, N-(coconut alkyl)-N,N,N-trimethyl methylammonium sulfate, cocamidopropyl betaine, hexadecyltrimethylammonium acetate and hexadecyltrimethylammonium nitrate; the complexing group is provided by the second modifier, and the second modifier includes one or more of polyacrylonitrile, poly(2-butenenitrile), poly(3-butenenitrile) and polymelamine.

10. The positive electrode sheet according to claim 9, wherein: Based on the total weight of the positive electrode active material layer, the weight content of the carbon nanotubes is 0.25%-1.5%, the weight content of the bonding layer is 0.25%-1.5%, and the weight content of the polymer additive is 0.1%-1%.

11. A battery, characterized in that: The battery comprises the battery according to any one of claims 1 to 10.

12. The battery according to claim 11, wherein The battery further includes an electrolyte, the electrolyte includes a cyano compound, and the cyano compound includes one or more of 1,4-dicyano-2-butene, succinonitrile, 1,3,6-hexanetrinitrile, 1,4-dicyano-2,3-dimethyl-2-butene and 1,2,3-tris(2-cyanoethoxy)propane; Preferably, based on the total weight of the electrolyte, the weight content of the cyanide-containing compound is 1%-10%.

Citation Information

Patent Citations

  • Battery positive electrode and battery

    CN115000405A

  • High-conductivity lithium ion battery positive electrode binder and preparation method thereof

    CN116814200A

  • Battery

    CN117728041A

  • Lithium secondary battery

    KR1020260058984A

  • Negative electrode and lithium battery including the same

    US20240322174A1

Cited By

  • Preparation method of high-load lithium iron phosphate positive plate

    CN121790323A